División social por estratos, materialismo y la situación de los perros en Colombia. (2019)
This paper examines a series of variables that influence the preference of purebred dogs in Colombia, and the role of social stratification regarding this matter. A quanti-tative methodology was elaborated using a structured questionnaire as data recollec-tion tool. The sample was made up of dog owners in Bogotá, the capital of Colombia, where the fieldwork was conducted. Through the SEM methodology, invariance test and a multiple-group analysis, the results show that materialism influences the social perception about purebred dogs; the dogs of more materialistic owners show greater behavioral problems, which influences owners’ intention to abandon them. In most of the cases, these behaviors are less intense in citizens of middle or high strata than in those living in lower strata.